Improving Digital Literacy of The Elderly Through a Participation-Based Approach: Service Program at Bekasi Elderly School - Muhammad Patria (Pusat Penelitian Pengabdian Pada Masyarakat Sekolah Tinggi Ilmu Tarbiyah Al-Fattah Siman Lamongan, 2025)
This Community Service Program aims to enhance the elderly’s ability to filter and respond to digital information through interactive training critically. The program was conducted at the Elderly School in Jatisampurna Subdistrict, Bekasi City, involving 50 participants. The implementation methods included socialization, training, technology application, mentoring, and evaluation. The materials covered the definition of hoaxes, their negative impacts, characteristics, and steps to verify information using technologies such as Google Fact Check and Turn Back Hoax. Evaluation results showed that 96% of participants were satisfied with the program. Additionally, digital literacy among participants significantly improved, with confidence in using technology increasing by 53%, the ability to verify information rising by 58%, and understanding of hoaxes increasing by 50%. This program had a positive impact by improving digital literacy and raising participants' awareness of the importance of verifying information before sharing it. The program is expected to serve as a model for digital literacy education that can be implemented for the elderly in other regions to mitigate the negative impacts of hoaxes and empower the elderly in the digital era.